The Role of Tutorials in Improving the Argumentative Skills of Secondary School Students - Podplota, Svitlana (Journal of History Culture and Art Research, 2020)
From the standpoint of the person-centered approach aimed at supporting students' active position and independence, the tutor's activity in the educational process of secondary school is revealed. The tutor plays a very important role in the formation of a student’s capability. Tutorials focus on improving students’ argumentative skills in a particular area of expertise, training self-reflection and teaching to put forward arguments. The article is devoted to peculiarities of applying the tutor's questioning techniques and writing essays in teaching argumentation to secondary school students. The research aims to identify the most effective ways and means of applying the given methods. The complex of modern general scientific methods has been used for task realization: theoretical methods – analysis and synthesis; empirical methods - observational (direct and indirect observation); diagnostic (expert interviews, conversations). As a conclusion, we note that conducting tutorials enables to reflect the theoretical foundations of argumentation and forms the research interest, stimulates the process of decentralization in the argumentation of students and also develops their own moral position.